Triangular Current Mode for High Step Ratio Modular Multilevel Dc-Dc Converter - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2018)
DC networks have generated much interest in recent years, from transmission in high voltage to their use in distribution systems. One of the major challenges is to replace the high efficient and reliable ac transformer, especially at high voltage and step ratio. New resonant modular multilevel topologies have arisen as an alternative, mainly because of advantages such as optional use of transformers, natural voltage balance, simple control and soft-switching. However, this type of operation generates a high peak current, does not allow control of power flow in all power range and has a limited range of voltage variation. This paper proposes an asymmetrical triangular current mode applied in high step ratio Modular Multilevel dc-dc Converters that achieves bidirectional control of the power, soft-switching and a natural balance of the voltage in the capacitors. The simulation results show the bidirectional operation and the capacitor voltage balance of the converter under different operating conditions with high efficiency and low peak current compared to resonant mode. The proposal was tested in a down-scale prototype, confirming the operation principle. © 2018 IEEE.
Keywords: DC-DC conversion; High step ratio conversion; Modular multilevel converter; Triangular current mode